Variability of functional outcome measures used in animal models of stroke and vascular cognitive impairment – a review of contemporary studies. Issue 11 (November 2018) - Hietamies, Tuuli M; Ostrowski, Caroline; Pei, Zhong; Feng, Luyang; McCabe, Christopher; Work, Lorraine M; Quinn, Terence J
Despite promising preclinical data, few novel stroke therapies have shown efficacy in man. Efforts to improve standards in conduct and reporting of preclinical research are ongoing. In clinical trials, inconsistency in outcome measures led to regulatory agencies and funders mandating use of a core set of functional outcomes. Our aim was to describe functional outcome measures in preclinical stroke and vascular cognitive impairment (VCI) studies. From 14 high impact journals (January 2005–December 2015 inclusive), 91, 956 papers were screened with 1302 full texts analyzed for stroke (ischemic and hemorrhagic) and 56 for VCI studies. In total, 636 (49%) stroke and 37 (66%) VCI papers reported functional outcome measures. There were 74 different functional assessments reported in stroke and 20 in VCI studies. Neurological deficit scores (74%) and Morris water maze (60%) were most commonly used in stroke and VCI, respectively. However, inconsistencies in methods used to assess and score recovery were noted. Neurological and behavioural functional outcome measures are increasingly used in preclinical stroke or VCI studies; however, there is substantial variation in methods. A strict standardized outcome set may not be suitable for translational work, but greater consistency in choice, application and reporting of outcomes may improve the science.